2016
DOI: 10.3201/eid2208.151895
|View full text |Cite
|
Sign up to set email alerts
|

Co-infections in Visceral Pentastomiasis, Democratic Republic of the Congo

Abstract: Results of PCR and histology indicate this infection is endemic to this country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…These records are the first to quantify the zoonotic threat from pythons and large-bodied vipers of the genus Bitis sold for human consumption at rural markets of the DRC. Our results are disturbing and are in line with new data indicating an increasing number of human pentastomid infections in this area (Tappe et al 2016). Consumption of snakes as bushmeat seems to be the general reason behind the emerging epidemics of human pentastomiasis.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These records are the first to quantify the zoonotic threat from pythons and large-bodied vipers of the genus Bitis sold for human consumption at rural markets of the DRC. Our results are disturbing and are in line with new data indicating an increasing number of human pentastomid infections in this area (Tappe et al 2016). Consumption of snakes as bushmeat seems to be the general reason behind the emerging epidemics of human pentastomiasis.…”
Section: Discussionsupporting
confidence: 85%
“…However, our data show that A. grandis prefers vipers and most vipers indeed host A. grandis, whereas A. armillatus prefers to parasitize pythons and accordingly, most pythons host A. armillatus. Our identification of parasite species was based only on morphology (the number of ring-like annulations), a field method that a recent molecular study had confirmed (Tappe et al 2016). To the best of our knowledge, host specificity of African Armillifer species has not been formerly tested using sample sizes comparable to ours.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An adult Armillifer grandis specimen was collected from the lungs of a rhinoceros viper (Bitis nasicornis) in the Democratic Republic of Congo near the town of Kole (3 27 0 37 00 N, 22 26 000 E, Sankuru district) and identified morphologically to species level (Tappe et al 2016). A voucher is deposited in the pentastomid collection of the Museum f€ ur Naturkunde Berlin (R€ ohlig et al 2010) under the accession ZMB 48784.…”
Section: Mitogenome Announcementmentioning
confidence: 99%
“…Serological and PCR tests specific to Armillifer are possible but not usually available. 4, 13,14 Patients may have a mild eosinophilia. 2, 4,11…”
Section: Discussionmentioning
confidence: 99%